Investigating the molecular mechanisms associated with ulcerative colitis through the application of single-cell combined spatial transcriptome sequencing - Huang, Hua; Ma, Jiaze; Kang, An; Guo, Tianwei; Sun, Wei; Xu, Yan; Ji, Lijiang (Frontiers in Immunology, 2025)
BackgroundUlcerative colitis (UC) is a chronic inflammatory bowel disease marked by dysregulated immune responses, resulting in sustained inflammation and ulceration of the colonic and rectal mucosa. To elucidate the cellular subtypes and gene expression profiles implicated in the pathogenesis of UC, we utilized single-cell and spatial transcriptomic analyses.MethodsWe conducted an analysis of single-cell data to identify cell types involved in the pathogenesis of UC. Employing machine learning methodologies, we screened for key genes implicated in UC and validated these findings through spatial transcriptomics. Additionally, immunohistochemistry was performed on UC lesion samples to investigate the expression patterns of the identified key genes. In an animal model, we utilized immunofluorescence and western blotting to validate the expression of these genes in the affected intestinal segments.ResultsOur investigation identified specific monocyte subtypes associated with UC through a comprehensive analysis involving cell communication, Least Absolute Shrinkage and Selection Operator (LASSO), and Support Vector Machine (SVM) methodologies. Notably, two genes, G protein subunit gamma 5 (GNG5) and tissue inhibitor of metalloproteinase 1 (TIMP1), were identified as key regulators of UC development. Spatial transcriptomic indicated a downregulation of GNG5 expression in UC, whereas TIMP1 expression was upregulated. Furthermore, a significant correlation was detected between TIMP1 and T cell exhaustion-related genes such as genes related to T cell exhaustion, including T cell immunoreceptor with Ig and ITIM domains (TIGIT) and cytotoxic T-lymphocyte-associated protein 4 (CTLA4). Immunohistochemical analysis of UC lesion samples revealed diminished expression levels of GNG5 and elevated expression levels of TIMP1. A dextran sulfate sodium (DSS)-induced colitis mouse model was developed, demonstrating that the protein expression levels of GNG5 in the colonic tissue of model mice were significantly decreased compared to controls w)ile the expression levels of TIMP1 were increased (p < 0.01). Furthermore, immunofluorescence staining indicated co-localization of TIMP1 with the macrophage marker F4/80 in monocytes.ConclusionOur research delineated distinct monocyte subtypes correlated with UC and identified two pivotal genes, GNG5 and TIMP1, that contribute to the disease’s pathogenesis. These insights offer a significant theoretical basis for enhancing the clinical diagnosis and therapeutic strategies for patients with UC.